Perancangan Sistem Informasi Akuntansi Penerimaan Dan Pengeluaran Kas di PT. Koprima Sandysejahtera Bandung - Putri, Syifa Nur Alya; Muthmainnah,; Sufyana, Candra Mecca (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
This research aims to create an accounting information system for receipts and disbursements. The data collection methods used are observation, interviews, documentation and literature related to the problem. The results of research conducted at PT. Koprima Sandysejahtera showed that the processing of receipts and disbursements data was still done manually, so it was necessary to design an accounting information system to facilitate these activities. The Waterfall method is used for software development. The models used are Flowmap, Data Flow Diagrams and Entity Relationship Diagrams which are then implemented using web programming language and MySQL as the database. This research resulted in the creation of an accounting information system for cash receipts and disbursements at PT. Koprima Sandysejahtera by facilitating the process of data entry, data processing and reporting. By making this system capable of producing reports more efficiently, quickly, easily and accurately.
Keywords: Accounting; Information System; Cash Receipt; Cash Disbursement